The Sensory and Perceptual Scaffolding of Absorption, Inner Speech, and Self in Psychosis - Rosen, Cherise; Tufano, Michele; Humpston, Clara S.; Chase, Kayla A.; Jones, Nev; Abramowitz, Amy C.; Franco Chakkalakal, Ann; Sharma, Rajiv P. (Frontiers in Psychiatry, 2021)
Abstract Background: This is the first study to examine the interconnectedness between absorption/immersion, inner speech and psychopathology. Absorption involves immersion in mental imagery, sensory/perceptual stimuli, or vivid imagination that involves decreased self-awareness and alterations in consciousness. In psychosis, changes in intrapsychic, self-other and inter-object boundaries redefine reality. Sense of self and ‘meaning making’ of these alterations is a ‘dialogical’ process consisting of ongoing inner dialogue and dialogue with others. Methods: This study consisted of 117 participants; 81 participants with psychosis and 36 controls. We first conducted a bivariate correlation to elucidate the relationship between absorption and inner speech. We next conducted hierarchical multiple regressions to examine the effect of immersion and inner speech to predict psychopathology. Lastly, we conducted a network analysis and applied extended Bayesian Information Criterion to select the best model. Results: In psychosis, we showed that dialogical and emotional/motivational types of inner speech were strongly associated with all immersion subscales, while condensed inner speech was singularly associated with increased imaginative involvement. We also demonstrated that altered consciousness, dialogical and emotional/motivational inner speech all predicted positive symptoms. In terms of network associations, imaginative involvement was the most central, influential, and most highly predictive node in the model from which all other nodes related to inner speech and psychopathology are connected. Conclusion: This study shows that within the network of immersion, inner speech and psychopathology, vivid sensory and perceptual imaginative involvement that encompasses dialogical inner speech with evaluative and motivational characteristics as expressed in alteration of consciousness is an interconnected structure in psychotic experiences.